Novel fused pyrimidine and isoquinoline derivatives as potent HIV-1 NNRTIs: a patent evaluation of WO2016105532A1, WO2016105534A1 and WO2016105564A1. (3rd April 2017) - Kang, Dongwei; Huo, Zhipeng; Wu, Gaochan; Xu, Jiabao; Zhan, Peng; Liu, Xinyong
ABSTRACT: Introduction: In the three patent applications, the impact of changing the pyrimidine core of the rilpivirine (RPV) to a variety of alternative fused cores was explored, culminating in the identification of a series of conformationally restricted compounds with comparable potencies against WT and mutant HIV-1 strains with those of efavirenz (EFV) and RPV, and higher security in the Human Ether-a-go-go-Related Gene (hERG) assay. Areas covered: The present review provides a fused pyrimidine and isoquinoline derivatives as potent HIV-1 NNRTIs, and highlights the conformational restriction strategies in the development of NNRTIs. Expert opinion: The molecular docking analysis of the newly synthesized compounds maintain the classical horseshoe conformation and shares similar binding mode with RPV. The conformational restriction strategies have greatly accelerated the optimization of the DAPY NNRTIs and contribute to finding new chemical entities (NCEs) with favorable druggability.